Education longitudinal studies in Brazil: literature review of the methodological approach and educational data use for education researches - Tatiana Figueroa Martin Gaya; Ana Lorena Bruel (Red Latinoamericana de Estudios Epistemológicos en Política Educativa, 2019)
This article presents a literature review on the longitudinal approach research methodology used in education researches in Brazil. It was considered as necessary to identify studies with such methodology, since this perspective is not commonly used in education researches in Brazil. The following repositories were used: Scielo, the CAPES scientific journals Bank and the CAPES Thesis and Dissertation Bank. For the papers selection, the following descriptors were used: "longitudinal studies", "longitudinal study", "Brazil" and "education". Twenty papers, published between 2000 and 2017, were selected for an in-depth analysis with the purpose of describing these studies characteristics and possibilities presented with this research methodology. Finally, we propose using the School Census data, collected by the National Institute of Educational Studies and Researches Anísio Teixeira (INEP) to conduct researches with a longitudinal approach in education.